2020
DOI: 10.1101/2020.06.23.167601
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptomic and proteomic regulation through abundant, dynamic, and independent arginine methylation by Type I and Type II PRMTs

Abstract: Arginine methylation is essential for both cellular viability and development and is also dysregulated in cancer. PRMTs catalyze the post translational monomethylation (Rme1/MMA, catalyzed by Type I-III), asymmetric (Rme2a/ADMA, Type I enzymes)-, or symmetric (Rme2s/SDMA, Type II enzymes) dimethylation of arginine. Despite many studies, a thorough integration of PRMT enzyme substrate determination and proteomic and transcriptomic consequences of inhibiting Type I and II PRMTs is lacking. To characterize cellul… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…Additionally, by western blot these Sm proteins had reduced Rme2s (Figure 3a, middle panel) . Furthermore, consistent with the ability of different classes of PRMTs to scavenge each other’s substrates (Dhar et al 2013; Lehman et al 2020), we observed an increase in Rme2a with GSK591. We also noted an increase in Rme2s in the MS023-treated A549 cells (Figure 3a) .…”
Section: Resultssupporting
confidence: 85%
“…Additionally, by western blot these Sm proteins had reduced Rme2s (Figure 3a, middle panel) . Furthermore, consistent with the ability of different classes of PRMTs to scavenge each other’s substrates (Dhar et al 2013; Lehman et al 2020), we observed an increase in Rme2a with GSK591. We also noted an increase in Rme2s in the MS023-treated A549 cells (Figure 3a) .…”
Section: Resultssupporting
confidence: 85%
“…In agreement with the latter, we found increase of all differentiated IEC lineages after treatment with MS023 ( Figures 6A–F ). PRMT1 has a wide substrate specificity and mediates both arginine methylation of histones such as H4R3, and non-histone proteins (Huang et al, 2005 ; Lehman et al, 2020 ). Elevated PRMT1 expression is found in several cancer types and is associated with poor prognosis and chemoinsensitivity (Altan et al, 2016 ; Musiani et al, 2020 ) and pharmacological PRMT inhibitors have recently gained interest as drug candidates for cancer treatment (Guccione and Richard, 2019 ; Jarrold and Davies, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…6a-6f ). PRMT1 has a wide substrate specificity and mediates both arginine methylation of histones such as H4R3, and non-histone proteins 64,65 . Elevated PRMT1 expression is found in several cancer types and is associated with poor prognosis and chemoinsensitivity 66,67 and pharmacological PRMT inhibitors have recently gained interest as drug candidates for cancer treatment 43,45 .…”
Section: Discussionmentioning
confidence: 99%